The differences between double and single leg takeoff on joint kinetics during rebound-type jump - Kariyama, Y.; Mori K.; Ogata, M. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The purpose of this study was to identify the differences between double and single leg takeoff on joint kinetics during a rebound-type jump. Twelve male track and field athletes performed repeated rebound-type jumps with double legs (DRJ) and a single leg (SRJ). Kinematics and kinetics data were recorded using a high-speed video camera (300 Hz) and force platforms (1000 Hz). The negative and the positive values of the joint torque power about the ankle joint were significantly lower in DRJ than in SRJ. However, the mean joint extension torque, and the negative value of the joint torque power about the hip joint was larger in SRJ than in DRJ. It is suggested that the joint kinetics characteristics, in SRJ as compared to DRJ, reveals a relatively large joint torque and torque power about the hip joint.